Buy British campaign - NUHKW leaflet, 1981 (London, 1981)
1981 1980-95 "Buy British campaign - NUHKW leaflet, 1981" [BW0184], 1981, Trades Union Congress This leaflet publicises a march and rally in Nottingham, organised by the National Union of Hosiery and Knitwear Workers on 13 March 1981 in support of a campaign to buy British made goods. The union called for import controls to restrict cheaper imported goods which they said had a negative effect on employment in the clothing and textile industries, particularly in the East Midlands.